1981
DOI: 10.1128/jvi.38.3.880-885.1981
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation characteristics of newly synthesized Epstein-Barr viral DNA in superinfected cells

Abstract: Replicating Epstein-Barr virus (EBV) DNA molecules isolated from superinfected Raji cells were shown to consist of 80S to 65S and 58S (mature) molecules. Pulse-chase experiments showed that radioactive label of DNA molecules with the larger sedimentation coefficients was partially chased into 58S labeled forms. Formation of large concatemers of viral DNA could not be detected at any time after superinfection. The continuous presence of the 65S viral DNA intermediate throughout the replicative cycle combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…(The experiments were done before recombinant EBV DNA clones were available.) Siegel and co-workers looked at the size of replicating viral DNA in superinfected Raji cells (14); there appeared to be several size classes, one of which could possibly be defective DNA. Why does standard HR-1 DNA not replicate upon superinfection of X50-7 cells?…”
Section: R P3r3mentioning
confidence: 99%
“…(The experiments were done before recombinant EBV DNA clones were available.) Siegel and co-workers looked at the size of replicating viral DNA in superinfected Raji cells (14); there appeared to be several size classes, one of which could possibly be defective DNA. Why does standard HR-1 DNA not replicate upon superinfection of X50-7 cells?…”
Section: R P3r3mentioning
confidence: 99%
“…Epstein-Barr virus is spontaneously reactivated leading to lytic antigen expression. In cases in which lytic antigen expression culminates in the production of virions, the presence of linear genomes can be demonstrated (22). In vitro studies have shown that acyclovir is effective only in reducing the number of linear replicative Epstein-Barr virus genomes (19,23).…”
Section: Discussionmentioning
confidence: 99%
“…When latency is disrupted by cryptic signals that occasionally activate viral genes (21) during the early S phase (22), a multitude of virus-induced proteins is expressed, including a DNA polymerase (11,12,17,39) which amplifies the number of copies of circular EBV DNA (50). The circular genomes synthesized by the viral enzyme (50,53) are presumably precursors of the linear DNA in virions.…”
mentioning
confidence: 99%